THE PATH OF A GENOCIDE: THE RWANDAN CRISIS FROM UGANDA TO ZAIRE (Hekima Review, 2024)
Is there anything new to be written about the 1994 genocide in Rwanda? There is some truth in the claim that dynamic scholarship is born out of crisi-certainly this seems to be the case with regard to post-genocide Rwanda. Since 1995, every year there is at least one publication on the Rwandan crisis stressing various dimensions of the crisis.